Pemikiran Dan Teori Tafsir Nasr Hamd Abu Zaid - M Shofiyyuddin (Institut Islam Nahdlatul Ulama Temanggung, 2018)
This article examines the theories used by Nasr Hamd Abu Zaid in understanding and interpreting the Qur’an. Nasr Hamd built his theological building by understanding the muktazilah with his affalizative nature to avoid tadadul qudama. Nasr Hamd combines al jurjani’s theory with Ferdinand de sausure’s theory of the relationship of signs and markers through cultural conventions. Nasr Hamd also used the theory of Linguistic Principles (Grammatical) and Psychological Principles (psychic) to enter the “door” of i’jaz and integrate with Desaussure’s theory of the distinction between langue, or what is known in Arabic is lisan, and the parole or known Arabic kalam. The i’jaz theory is not only approached with modern theories, but also with al jurjani’s al nadzm theory and is also distinctively nahwu and usul al nahwu. nasr hamd neatly and admirably tries to understand the classical interpretation theory with modern theories, so that these theories can be read scientifically by people today.